The Effectiveness of Training Based on the Principles of the Theory of Trees for Solving Problems in Providing High School Students in Jordan With the Skills of Inventive Thinking - Al-Bhayrat, Raed (Dirasat: Educational Sciences, 2021)
This study aims at recognizing the effect of training depending on Triz theory to solve the problems of imparting inventive thinking to first-secondary students. To achieve the objectives of the study, the researcher constructed a scale of inventive performance thinking and a training program depending on the principles of Triz theory, used the quasi-experimental method, and the sample of the study consisted of (100) students. The study found that there are significant statistical differences at (0.01) in all skills and on the scale as a whole in the students of the experimental groups. There are significant statistical differences at (0.05) among the means of the scores of students in the experimental groups in the post-test in both genders in the sum score on the inventive thinking scale and the in favor of males. Based on the results of the study, the researcher recommends encouraging learners to be inventive and seek knowledge in various fields, training them on problem-solving and offering them the opportunity to practice thinking skills such as inventive thinking besides conducting similar research studies.